CRITICAL DISCOURSE ANALYSIS: THEORY AND METHOD IN SOCIAL AND LITERARY FRAMEWORK - Ulinnuha, Roma (Universitas Pendidikan Indonesia, 2013)
Abstract: Critical Discourse Analysis (CDA) serves as one of the tools to analyzethe linguistic and the social. This article aims at investigating the relevance of ideasamongst CDA figures—Fairclough, Van Dijk, Wodak, and Kristeva—to both socialand literary studies. This includes some significant points such as discourse, socialpractice, representation, power and intertextuality. The article shows, based on literarystudy, the aim of CDA applied linguistic aspect is to reveal the hidden in the analyticallevel of individual, institutional or social, i.e. domination and the abuse of power. CDAfigures agreed to some extent that the complex interactions of discourse and socialcould not be analyzed, unless it utilized the approaches of linguistic and social. In thecourse of identity, for instance, CDA abridges the social and the linguistic realm. CDA,in this regard, mainly advocates the under-privileged representations of everyday life.